The Pacific Speed of Growth : How Fast Can It Be and What Determines It? - Yang, Yongzheng; Chen, Hong.; Singh, Baljeet; Singh, Shiu raj. (Washington, D.C. : International Monetary Fund, 2013)
This study aims to test within a relatively homogeneous group of small states what differentiates the growth performance of Pacific island countries (PICs) from their peers. We find that PICs are disadvantaged by distance and hampered by lower investment and exports compared with other small island states, but greater political stability, catch-up effects from lower initial incomes, and slower population growth have helped offset some of these disadvantages. On balance, policy-related factors, together with geography-related disadvantages, have led to growth rates in PICs that are much lower than in other small states. We also examine how real exchange rate appreciation, unfavorable developments in the external trade environment, and rising international transport costs may have contributed to PICs' slower growth over the past decade.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet